2021
DOI: 10.1002/fsn3.2470
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of Lactobacillus acidophilus LA‐5 and Bifidobacterium animalis BB‐12 in pectin and sodium alginate: A comparative study on viability, stability, and structure

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 49 publications
(99 reference statements)
1
8
0
Order By: Relevance
“…The encapsulation efficiency of L. acidophilus was 92.3% for the alginate as a single carrier, similar to the results observed by Moghanjougi et al [ 13 ] by 95.5% for L. acidophilus and Jouki et al [ 16 ] by 93.1% for Lactobacillus casei in alginate beads. The encapsulation efficiency of L. acidophilus significantly increased along with the increase of concentration of fish gelatin from 92.3 to 98.68% ( Table 1 ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The encapsulation efficiency of L. acidophilus was 92.3% for the alginate as a single carrier, similar to the results observed by Moghanjougi et al [ 13 ] by 95.5% for L. acidophilus and Jouki et al [ 16 ] by 93.1% for Lactobacillus casei in alginate beads. The encapsulation efficiency of L. acidophilus significantly increased along with the increase of concentration of fish gelatin from 92.3 to 98.68% ( Table 1 ).…”
Section: Resultssupporting
confidence: 88%
“…L. acidophilus was microencapsulated in sodium alginate according to the emulsion method defined by Moghanjougi et al [ 13 ] with minor modifications. Firstly, sodium alginate (2% w / v ) and fish gelatin (0.5, 1.5, and 3% w / v ) solutions were separately prepared in deionized water and sterilized at 121 °C for 15 min (15 psi).…”
Section: Methodsmentioning
confidence: 99%
“…This yield was smaller than the value we obtained in this work with the two different pretreatment methods (AM and UT), despite not having subjected the capsules to any coating. It is known that the encapsulation efficiency is influenced and depends on various factors such as the alginate concentration (wall material), the concentration and species of the probiotic cells, the content of calcium chloride, and the hardening time after encapsulation [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beads made up of sodium alginate and amidated low-methoxyl pectin in the ratios of 1:4 and 1:6 provided improved resistance to the entrapped Lactobacillus casei in simulated gastric and bile salt condition significantly (Sandoval-Castilla et al, 2010 ). Moghanjougi et al ( 2021 ) reported that pectin nanoparticles were resistant to both enzymatic and acidic conditions thus the microcapsules could be released in the colon environment, whereas alginate was suitable for encapsulation of probiotic bacteria Lactobacillus acidophilus under acidic conditions due to the conversion into insoluble alginic acid. The coating of whey protein concentrate and pectin did not provide additional protection to the probiotics in simulated GI conditions despite the higher survivability of probiotics (8 log CFU/g) after encapsulation (Gebara et al, 2013 ).…”
Section: Coating Materialsmentioning
confidence: 99%